2011
DOI: 10.3390/su3010270
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Regulation-Induced Innovation for Sustainable Development

Abstract: This article explores the complex relationship between environmental regulation, innovation, and sustainable development within the context of an increasingly globalizing economy. The economic development, environment, and employment aspects of sustainable development are emphasized. We contend that the most crucial problem in achieving sustainability is lock-in or path dependency due to (1) the failure to envision, design, and implement policies that achieve co-optimization, or the mutually reinforcing, of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(83 citation statements)
references
References 30 publications
(32 reference statements)
0
80
0
3
Order By: Relevance
“…The majority of these studies cited insufficient incentives to adopt environmentally sustainable practices as a trap and argued for greater economic incentives [30,32,38,42,45,55,63,66,67,69,74,75,83,84,95,102,117]. Some found that there were insufficient incentives to implement a policy or comply with regulations as a result of either a lack of official accountability or a lack of public demand for action [34,36,48,54,60,82,87,108,109]. Toke [82], for example, found that local communities received little direct benefit from windfarms in the UK and Denmark, resulting in a lack of incentive for their support.…”
Section: Implementation Trapsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of these studies cited insufficient incentives to adopt environmentally sustainable practices as a trap and argued for greater economic incentives [30,32,38,42,45,55,63,66,67,69,74,75,83,84,95,102,117]. Some found that there were insufficient incentives to implement a policy or comply with regulations as a result of either a lack of official accountability or a lack of public demand for action [34,36,48,54,60,82,87,108,109]. Toke [82], for example, found that local communities received little direct benefit from windfarms in the UK and Denmark, resulting in a lack of incentive for their support.…”
Section: Implementation Trapsmentioning
confidence: 99%
“…This may be the case for a single agency [31,35,37,45,46,48,60,90,93,102,104] or policies that require a multi-level or multi-sector approach to implementation [36,48,51,59,74,77,98,99,109,110,112]. Finally, problems also occur when the chain of responsibility for implementing a policy is unclear [41,48,61,74].…”
Section: Implementation Trapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Friendly economic growth emphasizes the importance of protecting the environment, and the coordinated economic development of urban agglomeration concerns the development gap among cities in urban agglomerations [17,18]. This paper employs spatial econometric methods and social network analysis in the GIS environment, in order to reveal the impact of environmental regulation on economic growth as well as the spillover effects due to disparity in environmental regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Vários estudos têm mostrado que quando a avaliação de impactos integra três fatores, quais sejam, econômico, social [particularmente saúde] e ambiental, como é o caso da avaliação de impacto da sustentabilidade [AIS], os impactos econômicos recebem mais atenção que os sociais e os ambientais (Morrisson--Saunders & Fischer, 2006;Smith, Fooks, Collin, Weishaar, & Gilmore, 2010), sendo um dos problemas cruciais para atingir a sustentabilidade o fato de que os interesses econômicos [e políticos] prevalecem no sistema atual e permanecem à frente do avanço de suas tendências sociais e ambientais (Ashford & Hall, 2011). Devido a essa realidade, para Morrisson-Saunders e Fischer (2006), a proteção do ambiente biofí-sico, mediante AIA e AAE, deve permanecer específica para esse fim.…”
Section: Limitações Da Avaliação De Impacto Ambiental (Aia) E Benefícunclassified